KERAGAMAN GENETIK EMPAT POPULASI Arenga pinnata MERR BERDASARKAN PENANDA ISOZIM - Liliek Haryjanto; Prastyono Prastyono; Burhan Ismail (Jurnal Pemuliaan Tanaman Hutan, 2011)
Aren tree or Sugar Palm (Arenga pinnata Merr) is one of bioethanol-producer which has advantages compared to other plant producing bioethanol. This study is  aimed to determine the genetic diversity of aren tree populations in its natural distribution. Genetic diversity of four populations were investigated by isozyme markers with 4 enzyme systems namely Esterase (EST), Glutamate oxaloacetate transaminase (GOT), Diaphorase (DIA) and 6-Phospogluconate dehydrogenase (6Pg). The number of alleles identified by 9 alleles are distributed on   four polymorphic loci. The research revealed that mean alleles per locus was 2,2500. The mean effective number of alleles per polymorphic locus was 1,8377. All loci were of  polymorphic. The mean genetic diversity within population was 0,4381and the proportion of genetic variation among populations was 0,0702. The UPGMA cluster analysis based on Nei’s standard genetic distance reflected two main clusters. The first cluster consisted of Central Java and South Kalimantan populations; while second cluster included the populations of Bengkulu and North Sulawesi.